2013
DOI: 10.1037/a0028325
|View full text |Cite
|
Sign up to set email alerts
|

Affective and cardiovascular responding to unpleasant events from adolescence to old age: Complexity of events matters.

Abstract: Two studies investigated the overpowering hypothesis as a possible explanation for the currently inconclusive empirical picture on age differences in affective responding to unpleasant events. The overpowering hypothesis predicts that age differences in affective responding are particularly evident in highly resource-demanding situations that overtax older adults' capacities. In Study 1, we used a mobile phone-based experience-sampling technology in 378 participants 14 -86 years of age. Participants reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 93 publications
8
89
2
Order By: Relevance
“…For example, in a study reviewed previously, compared with younger people, older adults showed reduced heart rate variability (i.e., poorer physiological regulation) only when they encountered stressor overloads (Wrzus et al, 2013). In another study of participants ranging from 34 to 85 years old, when adults older than 50 years experienced more distress than usual, they also had greater levels of daily cortisol output (Piazza, Charles, Stawski, & Almeida, 2013).…”
Section: Age-related Physical Vulnerabilities Make Regulating High Lementioning
confidence: 96%
“…For example, in a study reviewed previously, compared with younger people, older adults showed reduced heart rate variability (i.e., poorer physiological regulation) only when they encountered stressor overloads (Wrzus et al, 2013). In another study of participants ranging from 34 to 85 years old, when adults older than 50 years experienced more distress than usual, they also had greater levels of daily cortisol output (Piazza, Charles, Stawski, & Almeida, 2013).…”
Section: Age-related Physical Vulnerabilities Make Regulating High Lementioning
confidence: 96%
“…Older age has been linked with less stressor diversity, which predicts greater affective well-being [27]. In contrast, the ability to respond to stressors may be weakened in older age when negative events affect more than one life domain [28]. …”
Section: Emotion Regulationmentioning
confidence: 99%
“…In contrast, avoidance of interpersonal conflicts led to less reactivity in negative affect among older people (Charles et al, 2009). However, facing complex hassle situations (Wrzus et al, 2013) or experiencing intense sadness (Kunzmann & Grühn, 2005;Seider et al, 2011) led to stronger experiential and physiological reactivity among older people. Sadness is assumed to be highly relevant in older adulthood because of its association with loss and goal disengagement (Smith & Lazarus, 1993;Streubel & Kunzmann, 2011).…”
Section: Implications For Theories On Affective Developmentmentioning
confidence: 99%
“…Resulting from the acquired strengths and vulnerabilities, affective well-being is assumed to be more stable and better with older age as long as the emotional situation does not overtax the individual's limited resources; within these limits, reactivity to emotional situations should be less pronounced with older age. Yet when emotional situations exceed the available resources, high levels of distress, and/or of physiological arousal, are assumed to occur and to be more pronounced with older age (Charles & Luong, 2013;Labouvie-Vief, Gilet, & Mella, 2014;Wrzus, Müller, Wagner, Lindenberger, & Riediger, 2013). In addition, SAVI postulates that under the latter circumstances, people need more time to recover because of a diminished physiological flexibility and difficulties in dealing with highly distressing experiences.…”
mentioning
confidence: 99%